Social networking politeness in Malaysian news blogs / M Xavier Thayalan (Dr), Alice Shanthi and May Liu Siaw Mei - Thayalan, M Xavier; Shanthi, Alice; May, Liu Siaw Mei (2012)
Based on the premise that participants could disguise their identity and flame online interaction, the main aim of the study was to find out how Malaysians news bloggers observed politeness in online interaction, in addition to building a blog discourse community. Qualitative data was collected from annil.com an online Malaysian news blog. The speech acts identified in the qualitative data were categorized according to Brown and Levinson's (1978) categorization of politeness theory such as bald on-record strategy, positive politeness strategy, negative politeness strategy, and off-record-indirect strategy. In this study, it was found that each of the politeness strategies was manifested in the form of politeness tactics. For example, in the use of politeness strategy this study found at least nine different tactics such as the use of jokes, in-group markers, and showing of humility. By quantifying the qualitative data, the study found that the Malaysian news bloggers were generally polite with the use of positive politeness strategy and negative politeness strategy. The bloggers were also found to have social network in the building of a discourse community. Hence some bloggers were found to have served as gatekeepers to preserve harmony and to ensure blogging occurred in an environment that promoted friendship and camaraderie.